A fall prevention guideline for older adults living in long‐term care facilities. (12th September 2014) - Jung, D.; Shin, S.; Kim, H.
Abstract : Background: Falls are among the most frequent critical health problems for older adults over 65 years of age and often result in consequential injuries. Aim: This study developed a guideline covering risk factors and interventions for falls in order to prevent them from occurring in long‐term care facilities. Methods: This study was grounded in the methodological approach of the Scottish Intercollegiate Guideline Network for establishing evidence‐based guidelines: (1) establishment of the target population and scope of the guideline, (2) systematic literature review and critical analysis, (3) determination of the recommendation grade, (4) development of a draft nursing intervention guideline and algorithm, (5) expert evaluation of the draft nursing intervention guideline, and (6) confirmation of the final intervention guideline and completion of the algorithm. Results: The resulting evidence‐based fall prevention guideline consists of a three‐step factor assessment and a three‐step intervention approach. Limitations: The resulting guideline was based on the literature and clinical experts. Further research is required to test the guideline's feasibility in across long term care facilities. Conclusion: This guideline can be used by nurses to screen patients who are at a high risk of falling to provide patient interventions to help prevent falls. Implications for nursing and health policy: Considering the high rate of falls at long‐term care facilities and the absence of evidence‐based guidelines to prevent them, additional studies on falls at long‐term care facilities are necessary. Meanwhile, given prior research that indicates the importance of human resources in the application of such guidelines, continuous investigations are needed as to whether the research outcomes are actually conveyed to nurses.